Tunisia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2021)
The pandemic aggravated Tunisia's long-standing vulnerabilities stemming from persistent fiscal and external imbalances, rising debt, and contingent liabilities from inefficient state-owned enterprises. The crisis is expected to induce the largest contraction in real GDP since independence. The authorities' targeted response together with higher outlays on wages widened the fiscal deficit. A second Covid-19 wave is underway. The authorities are securing 500,000 doses to start a first campaign of vaccinations in February and are aiming to secure more doses to vaccinate half of the population starting in April-May. Staff expects GDP growth to rebound modestly in 2021, but it could take years before activity returns to pre-crisis levels, especially if large imbalances were not addressed and key reforms delayed. Downside risks dominate and recent protests highlight the level of social tensions, aggravated by Covid-19 restrictions, and particularly among the youth.